IMPACT OF SERVICE-LEARNING IMMERSION ACTIVITIES ON THE PERSPECTIVE TRANSFORMATION OF SHS STUDENTS: AN INSIDERS LENS - Therese D. San Juan, Frances; Kristopier D. Angeles, Juan (International Interdisciplinary Conference on Sustainable Development Goals, 2023)
The implementation of the K-12 Curriculum in 2016 is the most significant transformation in the Philippine educational system in the postcolonial era. Along with this change of curriculum is the supplemental two years (Grade 11 and Grade 11) to the former 11-year basic education system in the country. One of the academic strands in the K-12 curriculum is the Humanities and Social Sciences which includes subjects that require service-learning immersion activities that promote transformative learning. In recent years, transformative learning has been utilized by researchers in explaining adult learning. Transformative learning has been regarded as a "shift" in the traditional understanding of thoughts, feelings, and actions, which principles are founded by the early studies of Mezirow (1978, 1979).. In the service-learning context, the transformative learning model also explains how reflection and meaningful dialogues can facilitate more socially responsible community actions among students. However, service-learning educators have recently raised concerns about the need for more empirically driven research studies to continuously substantiate both the theory and the value of applying service-learning to K-12 and higher education. Furthermore, studies show that the adolescent population has been less commonly studied for transformative learning. Thus, using a qualitative lens, the researchers took deeper insights into the impact of service-learning immersion as culminating activities for a senior high school subject (Community Engagement, Solidarity, and Citizenship) on the perspective transformation of students. Findings revealed that their service-learning immersion experiences helped them achieve perspective transformation, even after the long hiatus brought on by the COVID-19 pandemic.